2006
DOI: 10.1007/s10522-006-9040-z
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine induces DNA damage and alterations in proliferative capacity of T-lymphocytes: a model for immunosenescence?

Abstract: Homocysteine (Hcy) appears to exert different effects on immune functions possibly contributing to age-related pathological states, including vascular diseases, immune dysfunction, and Alzheimer's disease. However, molecular mechanisms underlying Hcy toxicity need to be better characterized. Since T cells are a suitable model to address the possible role of replicative senescence during the in vivo aging, we investigated the effects of high Hcy concentrations on mitogen-activated lymphocytes, with regard to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Picerno et al (2007) showed that Hcy-treated human peripheral blood lymphocytes in culture presented increase in DNA damage and in micronucleus frequency, altering immune function. However, we did not discard other ways of action, considering that DNA strand breakage could be caused by nucleases activated by Ca 2+ and/or by ROS, mainly OH formed by reaction of H 2 O 2 with DNA-bound metal ions (Darley-Usmar and Halliwell, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Picerno et al (2007) showed that Hcy-treated human peripheral blood lymphocytes in culture presented increase in DNA damage and in micronucleus frequency, altering immune function. However, we did not discard other ways of action, considering that DNA strand breakage could be caused by nucleases activated by Ca 2+ and/or by ROS, mainly OH formed by reaction of H 2 O 2 with DNA-bound metal ions (Darley-Usmar and Halliwell, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore most likely that neurons undergoing apoptosis might form binucleated neurons. It has been shown that various factors cause apoptosis and binucleation in a variety of cells through the cytokinesis-blocking [13,14]. It is therefore suggested that some inflammatory assault might cause apoptosis and binucleation of neurons in NB.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been reported that human peripheral blood monocytes exposed to Hcy were unable to enter into mitosis (Picerno et al 2007). The mechanism is still not elucidated but it is known that high levels of the previously mentioned precursor of Hcy, S-adenosyl-L-Hcy can block phosphatidylinositol kinase, an enzyme responsible for second messenger signaling in cellular activation (Pike and DeMeester, 1988).…”
Section: Lymphocyte Proliferative Response To Piglet Sera From Differmentioning
confidence: 97%